2020
DOI: 10.1017/s0144686x20000902
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions and expectations of filial piety among older Chinese immigrants in Canada

Abstract: Much of the literature discusses filial piety in general and ambiguous terms. This study, in contrast, investigates specific perceptions of filial piety and parental expectations of filial duty among older Chinese immigrants in Canada. The study is based on thematic analysis of 46 Chinese immigrants in seven focus groups conducted in the Greater Toronto Area. Findings show the perceptions of filial piety varied, but almost all participants had reduced expectations of their children. Nevertheless, they still va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 91 publications
0
14
0
Order By: Relevance
“…Within Chinese collectivistic and Confucian culture, an individual's family role is one of the most significant identities (Zhang 2020). This is especially true for individuals who live in a hybrid mode of cultures, mediated between their country of origin and their country of residence (Luborsky and Sankar 1993;McDonald 2011).…”
Section: Older Family Membersmentioning
confidence: 99%
“…Within Chinese collectivistic and Confucian culture, an individual's family role is one of the most significant identities (Zhang 2020). This is especially true for individuals who live in a hybrid mode of cultures, mediated between their country of origin and their country of residence (Luborsky and Sankar 1993;McDonald 2011).…”
Section: Older Family Membersmentioning
confidence: 99%
“…Authoritarian FP emphasizes hierarchy and respecting parents obediently, however, adult children of various age groups may perceive this obligation differently as they belong to different generations. Studies have demonstrated that although older Chinese hold a strong belief in FP, they clearly expressed fewer expectations of filial duties from their adult children because the rapid social changes may lead to a lack of understanding of Confucian FPs in the younger generations [13,26,41]. Therefore, although they were committed to their older parents, they did not expect the same from their children [13].…”
Section: Discussionmentioning
confidence: 99%
“…From the Chinese perspective, a good death is commonly perceived as "a result of natural causes such as aging with a content life and no outstanding life regrets" [12]. However, considering the Chinese FP emphasizes etiquette before and after death [13], the attention paid to dealing with the dying process per se is surprisingly scarce. Moreover, the topic of death is regarded as taboo or a curse between parents and children [14,15].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations